Pengaruh Etnosentrisme Konsumen, Perceived Quality, dan Inovasi Produk Terhadap Keputusan Pembelian Produk Azarine - Sadira Hadriyani; Henryanto Abaharis (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study aims to determine the influence of consumer ethnocentrism, perceived quality, and product innovation on the purchase decision of azarine products. This type of research is quantitative with the object of the study, namely consumers who use azarine products. The data collection techniques carried out in this study are observation, questionnaire, and interview. The sampling technique used is a nonprobability sampling technique in the form of incidental sampling with a sample of 100 people. The results showed that the t-count value on consumer ethnocentrism of 3.266 was greater than the t-table of 1.985 with a significant value of 0.002 which was smaller than 0.05. Therefore, H0 is rejected and H1 is accepted, which means consumer ethnocentrism has a positive and significant effect on purchase decisions. In addition, perceived quality with a t-count value of 2.106 is greater than the t-table of 1.985 and a significant value of 0.038 which is less than 0.05, then H0 is rejected and H2 is accepted. As well as product innovations with a t-count value of 4.551 greater than t-table 1.985 and a significant value of 0.000 which is smaller than 0.05, H0 is rejected and H3 is accepted. Overall, the results of this study show that consumer ethnocentrism, perceived quality, and product innovation have a positive effect on the purchase decision of azarine products.